Perbandingan Algoritma Pengkodean Suara Manusia : Adaptive Delta Modulation and Linear Prediction Coding - Djadjat Sudaradjat (Paradigma, 2019)
Coding algorithms human voice with ADM (Adaptive Delta Modulation) and LPC (Linear Prediction Coding) made to the encoding signals digitally produced has bit rate as low as possible, thus saving bandwidth transmission line if it will be distributed to the transmission medium, and save memory or computer storage if it will be stored as data storage.ADM technique different from the LPC, the difference is generally classified on how it is encoded. If the ADM system which is encoded representation of the waveform so often called "waveform coding", while the system is encoded LPC are the parameters of the source of the human voice, so often called the "parametric coding".Human voice coding algorithms to be compared are the results of my own research when conducting studies Bachelor of Engineering and Master of Engineering at ITB. The results of measurements taken from the ADM system materials Bachelor of Engineering Thesis entitled "Low Bit-Rate Delta Modulation", while the LPC system is taken from the material Engineering Master's thesis with the title "Voice Signal Processing with LPC Method".From the measurement results ADM system can generate the bit rate of 16 Kbps, while the LPC system generates the bit rate of 2.4 Kbps with the sound quality is almost the same output quality human voice that can be understood (intelligible speech).